Influence of Thermal Management Strategy on Driving Range of Pure Electric Vehicle During Cold Start in Winter - Wang Moran; Dong Bin; Liang Kunfeng; Wang Lin; Liu Ruijian; Mi Guoqiang (Zhileng xuebao)
The driving range of pure electric vehicles (PEVs) significantly decreases in winter. In this study, a mathematical model of vehicle driving range considering the heat production of the battery and the load of the air conditioning was established to simulate and analyze the influence of heat pump heating, ambient temperature (AT) and cabin temperature (CT) on the driving range and the vehicle battery during the cold start under three driving conditions, namely, highway fuel economy test (HWFET)、new European driving cycle(NEDC)、China light-duty vehicle test cycle for passenger car (CLTC-P). Compared with the measured data, the simulation and experiment match well. The results show that the driving range decreases gradually with the decrease of AT and the increase of CT under three driving conditions. When the AT is 0 ℃ and the CT is 15 ℃, 20 ℃, and 25 ℃, the driving range of the China CLTC-P standard decreases by 21.46%, 27.74%, and 33.19%, respectively. The influences of three heat distribution strategies on driving range are different during the cold start of PEVs. During the cold start, when all the heat of heat pump is used to heat the battery, the battery power can be recovered properly. Under the driving conditions of NEDC and CLTC-P, the maximum state of charge (SOC) of the battery increases by 1.52% and 2.03% compared with the initial SOC. The driving range can be increased to a certain extent by using the heat pump.